Ateisme dalam Perspektif Barat dan Timur - Tonny Ilham Prayogo (Universitas Darussalam Gontor, 2019)
This article departs from an assumption regarding atheism is actually a part of ‎belief rejects the existence of God. Question about God is always interesting to be ‎discussed, in the case of some people believe in the existence of God and some others ‎reject it. So it is not surprising to find terms of theism (believe in God) and atheism (not ‎believing in God) altogether. This study initiated from Western and Eastern thought ‎about divinity and how they prove God’s existence. Western perspective is affirmed to ‎reject an existence of God. God is merely an abstract and has nothing to do with the ‎creation of the universe. While according to Eastern perspective, they believe in the ‎existence of God through a rational arguments that can be accepted by reason. ‎Accordingly, there are argumentations for sciences, knowledge, and nature creation ‎interrelated to an existence of Creator behind and that is “God